(untitled) (International Journal of Engineering and Computer Science, 2013)
One of the most important administrative developments in the developed as well as in developed countries has been the commencement and development of a large numbers of new projects in every field like agriculture, irrigation, industry, community, development, health and social welfare etc. The principle aims and objectives of all these programs have been to bring about overall changes in the exciting socio-economic structure in the country providing thereby dignified way of life to a citizen as a unit and socio economic upliftment of the world. So most of the administrators are directly concerned with the project administration than former activities. The potential of administrative system to formulate and implement, relevant and in viable project effectively constitutes a crucial element in the process of development. Development requires planning and planning includes a lot of projects.